Konteks Sosial Dalam Penamaan Anak Usia 0-3 Tahun (Kajian Sosiolinguistik) - Nuria Alfi Zahrah; Kanaya Afflaha Nissa (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Giving names to children basically involves the social background of their parents, some give names based on the good meaning of the name, social relations can include differences in names between regions, for example Sundanese and Javanese. The purpose of this study is to find out whether there is a social context behind the naming of children, the meaning of a name, and to find out whether all children's names are influenced by social context or not. Researchers collected data for review using online forms and interviews with parents of children aged 0-3 years, and then grouped them based on names that contained social contexts and names that did not contain social contexts. Then analyze why the social context occurs in naming children. The method used is the interview method (see) with note and record techniques. The results showed that the social context in naming children aged 0-3 years can be caused by parents who have different social backgrounds. However, nowadays it is difficult to find parents who give their children names using social contexts, most parents only name their children because of the meaning and meaning of the name.